High-strength cold-resistant water-pressure-resistant flame-retardant low-gram-weight chinlon fabric treatment glue solution and treatment method

By using high-strength cold-resistant, water pressure-resistant, flame-resistant, low-gps of glue treatment liquid on nylon fabrics, combined with the multi-layer coating process, the problem of difficulty in achieving versatility at the same time in existing fabrics is solved, and the fabric has been improved in multiple properties such as flame retardant, cold-resistant, water pressure resistance, wear resistance, and anti-adhesion, while maintaining a low grit.

CN119593224APending Publication Date: 2025-03-11DANDONG UNIK TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411762040.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When existing equipment and backpack fabrics integrate multifunctions, it is difficult to achieve excellent cold resistance, water pressure resistance, flame retardancy, high strength, wash resistance, wear resistance, and adhesion resistance, and maintain a low weight.

Method used

It uses a high-strength, cold-resistant, water-pressure flame-retardant, low-grain weight nylon fabric treatment solution, including flame-retardant primer and anti-adhesive surface glue. This glue solution achieves the improvement of the versatility of the fabric through the preparation of ultra-fine flame retardant powder, the selection and preparation of flame retardant primer and anti-adhesive surface coating, combined with waterproof finishing, calendering and multi-layer coating processes.

Benefits of technology

It has achieved significant improvements in flame retardant performance, tear strength, hydrostatic pressure, low temperature resistance and wear resistance, while maintaining a low weight, meeting the needs of high strength, wash resistance, wear resistance and adhesion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167948810000151
    Figure BDA0005167948810000151
  • Figure BDA0005167948810000161
    Figure BDA0005167948810000161
Patent Text Reader

Abstract

The embodiment of the invention discloses a high-strength cold-resistant water-pressure-resistant flame-retardant low-gram-weight chinlon fabric treatment glue solution and a treatment method. The treatment glue solution provided by the invention comprises the flame-retardant bottom coating glue and the anti-sticking surface coating glue, and after the chinlon fabric is treated, the obtained fabric keeps low gram weight and is obviously superior to an existing product in the aspects of flame retardance, tearing strength, hydrostatic pressure, low temperature resistance and wear resistance; the low gram weight, cold resistance, water pressure resistance, flame retardance, high strength, washing resistance, wear resistance and adhesion resistance are achieved at the same time, and good application prospects are achieved in the aspect of multifunctional integrated light fabric manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to the technical field of textile fabric finishing, and specifically to a high-strength, cold-resistant, water pressure-resistant, flame-retardant, low-weight nylon fabric treatment glue and a treatment method. Background Art

[0002] In recent years, with the continuous development of the cultural tourism industry and the acceleration of military modernization, higher requirements have been placed on the fabrics and functions of equipment and backpacks. Equipment and backpacks are no longer satisfied with one or two functions, but are required to integrate multiple functions in one, so as to better adapt to various environmental requirements and modern military training and battlefield requirements.

[0003] At present, the fabrics of equipment and backpacks mainly use high-strength nylon or polyester Oxford fabrics, which have excellent wear resistance, aging resistance, high strength and other properties. However, the high gram weight has always been the main problem. In addition, the high strength of the fabric itself will change after coating, which directly affects the durability of the fabric. In addition, it has always been a problem to achieve multiple functions at the same time. Some have solved the flame retardant problem through coating, but the gram weight is large and the water pressure resistance is poor; some have solved the low temperature resistance, but the flame retardant and anti-adhesion properties cannot be achieved. Therefore, it is of great significance to develop a lightweight fabric with excellent cold resistance, water pressure resistance, flame retardancy, high strength, washability, wear resistance, anti-adhesion, and low gram weight, which integrates multiple functions.

[0004] At present, there is no public information on the relevant technology for processing fabrics that have comprehensive cold resistance, water pressure resistance, flame retardancy, high strength, washability, wear resistance, anti-adhesion, and maintain a relatively low grammage. Summary of the invention

[0005] To this end, the embodiments of the present invention provide a high-strength, cold-resistant, water pressure-resistant, flame-retardant, low-weight nylon fabric treatment glue and treatment method. After being treated with the glue, the nylon fabric has excellent cold resistance, water pressure resistance, and flame retardancy, and is high in strength, washable, wear-resistant, and anti-adhesive, while maintaining a relatively low weight.

[0006] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:

[0007] According to a first aspect of an embodiment of the present invention, the present invention provides a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, including a flame-retardant base coating adhesive and an anti-stick surface coating adhesive;

[0008] The raw materials of the flame retardant primer include, by weight: 25-40 parts of toluene, 0.5-1.0 parts of dispersant, 40-50 parts of ultrafine flame retardant powder, 40-50 parts of two-component polyether polyurethane coating primer, 2.0-4.0 parts of diisobutyl nylonate, 2.0-3.0 parts of tearing agent, 3.2-4.0 parts of butylated melamine resin, 1.6-2.0 parts of p-toluenesulfonic acid catalyst, and 0.6-0.8 parts of aliphatic isocyanate crosslinking agent;

[0009] The raw materials of the anti-stick surface coating glue include, by weight: 30-50 parts of toluene, 0.2-0.5 parts of dispersant, 2.0-3.0 parts of high molecular weight spherical polyethylene powder, 3.0-5.0 parts of spherical silica, 100 parts of one-component polyether polyurethane coating surface glue, 0.5-1.0 parts of nylon acid diisobutyl ester, 1.0-2.0 parts of cross-linked silicone anti-stick agent, and 0.5-1.0 parts of aliphatic isocyanate cross-linking agent.

[0010] Furthermore, the ultrafine flame retardant powder is made of 60-90 parts of decabromodiphenylethane, 20-30 parts of antimony trioxide, and 20-30 parts of melamine cyanurate (MCA) as raw materials, and is ground into a particle size D 50 ≤1μm, and the ultrafine flame retardant powder is obtained.

[0011] Furthermore, 5-15 parts of antimony trioxide are replaced by an equal amount of zinc borate.

[0012] Further, the dispersant is a long-chain fatty amide solution;

[0013] The solid content of the one-component polyether polyurethane coating surface adhesive is (30±2)%;

[0014] The solid content of the two-component polyether polyurethane coating primer is (60±5)%;

[0015] The anti-tear agent is KSL-100;

[0016] The solid content of the butylated melamine resin is (54-60) %;

[0017] The solid content of the p-toluenesulfonic acid catalyst is (20±0.5)%;

[0018] The solid content of the aliphatic isocyanate crosslinking agent is (75±2)%;

[0019] The high molecular weight spherical polyethylene powder has a particle size D 50 ≤30μm;

[0020] The spherical silicon dioxide powder has a particle size D 50 ≤10μm;

[0021] The cross-linked silicone anti-adhesive agent is a cross-linked silicone resin with a molecular weight of 1500-2500. Furthermore, the preparation method of the flame-retardant primer includes: adding 0.5-1.0 parts of a dispersant to 25-30 parts of toluene, stirring to fully dissolve, then adding 40-50 parts of ultrafine flame retardant powder, dispersing until completely uniform; then adding 40-50 parts of a two-component polyether polyurethane coating primer, stirring evenly, then adding 2.0-4.0 parts of diisobutyl nylon acid, 2.0-3.0 parts of a tear inhibitor, 3.2-4.0 parts of butylated melamine resin, 1.6-2.0 parts of a p-toluenesulfonic acid catalyst and 0.6-0.8 parts of an aliphatic isocyanate cross-linking agent, stirring completely evenly, adding 0-10 parts of toluene, controlling the viscosity to 9000-10000cps, filtering the material, and obtaining the flame-retardant primer;

[0022] The preparation method of the anti-stick surface coating comprises: adding 0.2-0.5 parts of a dispersant into 30-40 parts of toluene, stirring to fully dissolve, then adding 2.0-3.0 parts of a high molecular weight spherical polyethylene powder, dispersing until completely uniform; then adding 3.0-5.0 parts of spherical silicon dioxide, continuing to disperse until completely uniform; then adding 100 parts of a one-component polyether polyurethane coating surface adhesive, stirring evenly, then adding 0.5-1.0 parts of nylon acid diisobutyl ester, 1.0-2.0 parts of a cross-linked organic silicon anti-sticking agent and 0.5-1.0 parts of an aliphatic isocyanate cross-linking agent, stirring evenly, adding 0-10 parts of toluene, controlling the viscosity to 7000-8000cps, filtering the material, and obtaining the anti-stick surface coating.

[0023] According to a second aspect of an embodiment of the present invention, the present invention provides the use of the high-strength, cold-resistant, water pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive as described in any of the above items in the production of equipment and backpacks.

[0024] Furthermore, the nylon fabric is 620D-650D high-strength nylon filament Oxford cloth.

[0025] According to a third aspect of an embodiment of the present invention, the present invention provides a method for processing a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric, the method comprising:

[0026] After the nylon fabric is subjected to waterproof finishing and calendering treatment, it is then coated in sequence with the flame retardant base coating adhesive and the anti-sticking surface coating adhesive as described in any of the above items.

[0027] Furthermore, the method comprises the following steps:

[0028] (1) Waterproof finishing: Use waterproof agent to pad the nylon fabric, double dip and double pad, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4;

[0029] (2) The waterproof fabric is calendered twice with a calender at a pressure of 9-11 MPa, a temperature of 150-170°C, and a speed of 20-30 m / min;

[0030] (3) First coat of flame retardant primer: The flame retardant primer is coated on the fabric treated in step (2) using a floating knife coating machine, and then dried at 130-140°C for 0.8-1.2 minutes to obtain a dry weight gain of 50-60 g / m 2 ;

[0031] (4) Second coat of flame retardant primer: The flame retardant primer is coated on the fabric treated in step (3) using a floating knife coating machine, and dried at 130-140°C for 0.8-1.2 minutes to a dry weight gain of 20-40 g / m 2 ;

[0032] (5) Anti-adhesive coating: The anti-adhesive coating is applied to the fabric treated in step (4) by a floating knife coating machine, and then dried at 150-165° C. for 1.0-1.2 minutes to obtain a dry weight gain of 8-10 g / m 2 .

[0033] Furthermore, the waterproofing agent is an organic fluorine waterproofing agent.

[0034] The flame retardants selected by the present invention are decabromodiphenylethane, antimony trioxide, and melamine cyanurate (MCA). Decabromodiphenylethane has a high bromine content, high flame retardant efficiency, good thermal stability, little effect on the mechanical properties of fabrics, low toxicity, and is environmentally friendly. When antimony trioxide is used in combination with decabromodiphenylethane, the flame retardant effect can be greatly improved, and it is selected as a flame retardant synergist. In some preferred embodiments, a portion of zinc borate is selected to be introduced into the synergistic flame retardant, which has multiple effects such as flame retardancy, carbonization, smoke suppression, smoldering suppression, and dripping prevention. Melamine cyanurate (MCA) can catalyze the degradation of nylon and react with it to form carbon through a cross-linking reaction.

[0035] The above flame retardants are used in combination. They can be decomposed into hydrogen bromide and antimony bromide during combustion. Hydrogen bromide can react with free radicals, antimony bromide can isolate oxygen and inhibit combustion. At the same time, MCA will produce non-combustible gases such as nitrogen and ammonia, forming an inert gas layer in the flame area. Several flame retardants play a flame retardant role in the gas phase at the same time. In addition, antimony bromide can further react with the carbon chain in the combustion product to generate non-combustible carbon bromide. At the same time, the combustion product of MAC can catalyze the degradation of nylon and react with it to form carbon by cross-linking, isolating oxygen and heat to wrap the surface of the combustion object, preventing oxygen and the combustion object from contacting, thereby playing a flame retardant role in the condensed phase. The gas phase and the condensed phase play a role at the same time, achieving the purpose of high-efficiency flame retardancy.

[0036] The preparation principle of the ultrafine flame retardant powder of the present invention is to utilize a mechanochemical method, that is, to apply mechanical energy to the flame retardant powder by means of friction, impact, and extrusion. On the one hand, the powder is ultrafine, and the particle size reaches less than 1 micron; on the other hand, the structure and physical and chemical properties of the flame retardant powder are induced to change, so that the surface activation energy of the powder is increased. The ultrafineness of the flame retardant powder can further increase the coverage and penetration of the fabric, thereby achieving the purpose of enhancing the flame retardant performance and reducing the amount of flame retardant powder used, so that a lower weight gain can achieve a better flame retardant effect, which is the most important control point for achieving a lower gram weight of the finished product. The increase in the surface activation energy of the powder is conducive to the combination of the flame retardant powder and the polyurethane colloid, and makes a great contribution to achieving good coating fastness.

[0037] The long-chain fatty amide solution dispersant selected by the present invention has high dispersing efficiency and anti-settling function. A large amount of flame retardant powder needs to be added to the primer of the present invention. The more evenly dispersed, the more evenly the flame retardant covers the fabric, which is more beneficial to the flame retardancy. At the same time, its good anti-settling effect can ensure the stability of the coating glue during use, and finally achieve a stable flame retardant effect.

[0038] The diisobutyl nylonate selected in the present invention is a plasticizer, commonly known as cold-resistant oil, and has excellent cold-resistant performance. When added to cold-resistant polyurethane, it can further improve the low-temperature flexibility of polyurethane film-forming, compensate for the influence of polyurethane cold resistance after adding flame retardant powder, thereby ensuring the cold resistance of the fabric.

[0039] The tear-resistant agent KSL-100 selected in the present invention is 100% organic silicon, has a smooth hand feeling, and has excellent tear-resistant effect. When added to the base coating, the polyurethane film can be smooth and full, and when applied to the fabric, the smooth hand feeling can reduce the constraint of the film on the yarn, and enhance the free stretchability of the yarn, thereby improving the tear strength of the fabric, achieving the purpose of high strength of the fabric after coating.

[0040] The butylated melamine resin selected by the present invention is the most efficient bridging agent for two-component polyurethane. The structure of the butylated melamine resin contains a large number of alkoxyl groups, imino groups or alkoxyl / NH functional groups, which can react with active groups such as amino groups, hydroxyl groups and carbamate groups in the two-component polyurethane. The resin has a fast curing speed and good film fastness. When a large amount of flame retardant powder is added to the primer, the resin can still maintain an excellent crosslinking degree, thereby achieving the purpose of continuous film formation, high water pressure resistance and excellent fastness.

[0041] The present invention uses p-toluenesulfonic acid as a catalyst, which is an organic strong acid and has a relatively high catalytic efficiency among acid catalysts. It can catalyze the reaction of polyurethane and butylated melamine resin in a polyurethane system and complete the reaction within 1 minute at 150-165°C.

[0042] The aliphatic isocyanate polyurethane crosslinking agent selected by the present invention has a large number of isocyanate (-NCO) functional groups, does not turn yellow, has high reactivity, reacts with active groups such as amino, hydroxyl, and carbamate in polyurethane, and acts together with butylated melamine resin to form a large spatial network structure, making the polyurethane film tougher, thereby achieving the purpose of making the fabric washable, wear-resistant, and durable.

[0043] The high molecular weight spherical polyethylene powder selected in the surface coating glue of the present invention has the characteristics of high temperature resistance, wear resistance and scratch resistance, which can give the coating surface the characteristics of toughness, scratch resistance and wear resistance, and improve the washing fastness and use performance of the fabric; its spherical particle shape can make it float on the surface of the coating film and be higher than the film surface, forming a micro-rough surface, which plays a certain role in dry feel and anti-adhesion.

[0044] The spherical silica powder used in the surface coating of the present invention is a highly effective anti-adhesive agent and lubricant. The addition of spherical silica can form a concave-convex surface on the coating surface. In addition, due to the high temperature resistance and dry feel, when the coating surfaces are attached together for hot pressing anti-adhesion test, on the one hand, the contact area between the coating surfaces can be reduced, and on the other hand, the part where the coating surfaces are attached together is heat-resistant and dry, and at the same time, it works together with the high molecular weight spherical polyethylene to achieve an anti-adhesion effect.

[0045] The cross-linked silicone anti-sticking agent used in the surface coating of the present invention is a low molecular weight cross-linked silicone resin, which has extremely low surface tension and high temperature cross-linking film-forming property, and can undergo cross-linking reaction with polyurethane to make the coating surface dry, smooth and anti-stick after the polyurethane film is formed.

[0046] The two-component polyether polyurethane coating primer selected by the present invention has excellent low-temperature flexibility and good cold resistance. At the same time, the film has a soft feel, high water pressure resistance, good bonding strength with the fabric, and is washable. Under the action of diisobutyl nylon acid, the cold resistance is further enhanced; under the joint action of butylated melamine resin, p-toluenesulfonic acid catalyst, and aliphatic isocyanate crosslinking agent, the film is more solid and can better form a coating for the flame retardant powder, achieving flame retardancy, water pressure, fastness, and cold resistance.

[0047] The viscosity of the flame retardant primer adhesive of the present invention is controlled at 9000-10000 cps, so that the coating adhesive can effectively penetrate into the yarn during coating, forming further wrapping of the yarn by the flame retardant adhesive, thereby achieving the purpose of excellent flame retardancy.

[0048] The one-liquid polyether polyurethane coating surface glue selected by the present invention has excellent low-temperature flexibility and good cold resistance. At the same time, its film-forming feel is dry, has high water pressure resistance, good bonding strength with the primer, and is washable. Under the action of nylon acid diisobutyl ester, the cold resistance is further enhanced; under the action of aliphatic isocyanate cross-linking agent, the film-forming is more solid and firm; under the joint action of high molecular weight spherical polyethylene powder, spherical silica powder, and cross-linked silicone anti-adhesive agent, the film-forming is more wear-resistant, scratch-resistant, and anti-adhesive.

[0049] In summary, the present invention prepares ultrafine flame retardant powder, selects flame retardant primer, selects anti-adhesion top coating, waterproof finishing, calendering twice, two-bottom and one-side coating process, so that the selected primer is under the condition of 130-140° C., under the action of butylated melamine resin and aliphatic isocyanate polyurethane crosslinking agent, under the catalysis of p-toluenesulfonic acid catalyst, nylon acid diisobutyl ester and anti-tearing agent are effectively bonded to the main chain of two-liquid polyether polyurethane coating primer, and under the action of long-chain fatty amide solution dispersant, the ultrafine flame retardant powder is tightly and evenly wrapped, and the primer is in an incompletely cross-linked state through temperature control; the selected top coating is under the condition of 150-165 Under the condition of ℃, under the action of aliphatic isocyanate polyurethane cross-linking agent, high molecular weight spherical polyethylene powder, spherical silica, nylon acid diisobutyl ester and cross-linked silicone anti-sticking agent are effectively bonded to the main chain of one-liquid polyether polyurethane coating surface glue; while forming the surface layer, under the action of high temperature, the selected primer and surface coating three-layer coating glue react and cross-link together, and at the same time react and cross-link with the amide group on the fabric to form a huge network structure. The raw materials work synergistically to form a tight and strong film, forming a coating film with excellent fastness, which is firmly combined with the fabric, so that the fabric has excellent cold resistance, water pressure resistance, flame retardancy, high strength, washability, wear resistance, anti-adhesion, and maintains a low gram weight.

[0050] The embodiments of the present invention have the following advantages:

[0051] After the nylon fabric is treated with the glue provided by the present invention, the obtained fabric maintains a relatively low gram weight and is significantly superior to existing products in terms of flame retardancy, tear strength, hydrostatic pressure, low temperature resistance and wear resistance, achieving low gram weight, cold resistance, water pressure resistance, flame retardancy, high strength, washability, wear resistance and anti-adhesion, and has good application prospects in the production of lightweight fabrics with multiple integrated functions. DETAILED DESCRIPTION

[0052] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] In the following content:

[0054] Decabromodiphenylethane, antimony trioxide, zinc borate, and melamine cyanurate (MCA) are commercially available, with a particle size of D 50 ≤5μm;

[0055] Toluene is commercially available, CAS No. 108-88-3;

[0056] The dispersant is a long-chain fatty amide solution, selected from the anti-settling dispersant DL P963 of Shenyang Keke Trading Co., Ltd.;

[0057] Two-component polyether polyurethane coating primer, solid content (60±5)%, selected from Liaoning Hengxing Fine Chemical Co., Ltd. product coating primer FS-5501C;

[0058] One-component polyether polyurethane coating surface adhesive, solid content (30±2)%, selected from Liaoning Hengxing Fine Chemical Co., Ltd. product coating surface adhesive JYK-C-3;

[0059] Nylon acid diisobutyl ester, commercially available, CAS No. 60209-70-3;

[0060] Anti-tear agent, solid content 100%, selected from the anti-tear agent KSL-100 produced by Wujiang Jielihui Textile Auxiliary Co., Ltd.;

[0061] Butylated melamine resin, solid content (54-60)%, selected from crosslinker DF-896 of Liaoning Hengxing Fine Chemical Co., Ltd.;

[0062] p-Toluenesulfonic acid catalyst, solid content (20±0.5)%, selected from Liaoning Hengxing Fine Chemical Co., Ltd. product crosslinker DF-899;

[0063] Aliphatic isocyanate crosslinking agent, solid content (75±2)%, selected from crosslinking agent DF-897 of Liaoning Hengxing Fine Chemical Co., Ltd.;

[0064] High molecular weight spherical polyethylene powder, particle size D 50 ≤30μm, selected from Shanghai Base Material Chemical Co., Ltd. high molecular weight polyethylene powder Texture5374W;

[0065] Spherical silica powder, particle size D50 ≤10μm, selected from spherical silica SN-Q55 of Guangzhou Shenna Trading Co., Ltd.;

[0066] Cross-linked silicone anti-adhesive agent, low molecular weight 1500-2500, selected from Guangzhou Silok Polymer Co., Ltd. Silok46;

[0067] The waterproofing agent is selected from the waterproofing agent TG-5601 produced by Daikin Fluorochemical (China) Co., Ltd.

[0068] Unless otherwise specified, “parts” in the following contents refer to “parts by weight”.

[0069] Example 1

[0070] The present embodiment provides a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, including: a flame-retardant base coating adhesive and an anti-stick surface coating adhesive.

[0071] (1) Preparation of ultrafine flame retardant powder

[0072] Raw materials by weight

[0073] 60 parts of decabromodiphenylethane, 15 parts of antimony trioxide, 10 parts of zinc borate and 20 parts of melamine cyanurate (MCA) were put into a planetary ball mill and ground for 10 hours. The particle size was D 50 0.8μm, ultra-fine flame retardant powder.

[0074] (2) Preparation of flame retardant primer

[0075] Raw materials by weight

[0076] Take 25 parts of toluene, add 0.5 parts of dispersant into toluene, stir to fully dissolve, then add 40 parts of ultrafine flame retardant powder obtained in the above step (1), disperse until completely uniform; then add 45 parts of two-component polyether polyurethane coating primer, stir evenly, then add 2.2 parts of nylon acid diisobutyl ester, 2.5 parts of tear inhibitor, 3.6 parts of butylated melamine resin, 1.8 parts of p-toluenesulfonic acid catalyst, 0.6 parts of aliphatic isocyanate crosslinking agent, stir completely evenly, add 2.0 parts of toluene, control the viscosity of the primer to 9200cps, filter the material, and obtain a flame retardant primer.

[0077] (3) Preparation of anti-stick surface coating

[0078] Raw materials by weight

[0079] Take 30 parts of toluene, add 0.3 parts of dispersant into toluene, stir to fully dissolve, then add 2.5 parts of high molecular weight spherical polyethylene powder, disperse until completely uniform; then add 4.0 parts of spherical silica, continue to disperse until completely uniform; then add 100 parts of one-component polyether polyurethane coating surface glue, stir evenly, then add 0.7 parts of nylon acid diisobutyl ester, 1.2 parts of cross-linked silicone anti-sticking agent, 0.5 parts of aliphatic isocyanate cross-linking agent, stir completely evenly, add 5.0 parts of toluene, control the surface coating viscosity to 7300cps, filter the material to obtain anti-stick surface coating glue.

[0080] This embodiment provides a nylon fabric processing method based on the above-mentioned glue:

[0081] (1) Waterproof finishing: Use waterproof agent to pad the 620D high-strength nylon filament Oxford cloth, double dip and double padding, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4;

[0082] (2) The waterproof fabric is calendered twice with a calender at a pressure of 10 MPa, a temperature of 150°C, and a speed of 30 m / min;

[0083] (3) First coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (2) using a floating knife coating machine, dry at 130-140°C for 0.8 minutes, and dry weight gain of 52 g / m 2 ;

[0084] (4) Second coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (3) above using a floating knife coating machine, dry at 130-140°C for 1.0 minute, and dry weight gain of 30 g / m 2 ;

[0085] (5) Anti-adhesive coating: The anti-adhesive coating in the treated glue solution is applied to the fabric treated in step (4) above by a floating knife coating machine, and then dried at 150-165°C for 1.0 minute to obtain a dry weight gain of 9 g / m 2 .

[0086] Example 2

[0087] The present embodiment provides a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, including: a flame-retardant base coating adhesive and an anti-stick surface coating adhesive.

[0088] (1) Preparation of ultrafine flame retardant powder

[0089] Raw materials by weight

[0090] 70 parts of decabromodiphenylethane, 23 parts of antimony trioxide, and 25 parts of melamine cyanurate (MCA) were put into a planetary ball mill and ground for 12 hours. The particle size was D 50 0.7μm, ultra-fine flame retardant powder.

[0091] (2) Preparation of flame retardant primer

[0092] Raw materials by weight

[0093] Take 27 parts of toluene, add 0.7 parts of dispersant into toluene, stir to fully dissolve, then add 40 parts of ultrafine flame retardant powder obtained in the above step (1), disperse until completely uniform; then add 50 parts of two-component polyether polyurethane coating primer, stir evenly, then add 2.0 parts of nylon acid diisobutyl ester, 2.0 parts of tearing agent, 4.0 parts of butylated melamine resin, 2.0 parts of p-toluenesulfonic acid catalyst, 0.75 parts of aliphatic isocyanate crosslinking agent, stir completely evenly, add 3.0 parts of toluene, control the viscosity of the primer to 9500cps, filter the material, and obtain a flame retardant primer.

[0094] (3) Preparation of anti-stick surface coating

[0095] Raw materials by weight

[0096] Take 32 parts of toluene, add 0.5 parts of dispersant to toluene, stir to fully dissolve, then add 2.0 parts of high molecular weight spherical polyethylene powder, disperse until completely uniform; then add 5.0 parts of spherical silica, continue to disperse until completely uniform; then add 100 parts of one-liquid polyether polyurethane coating surface glue, stir evenly, then add 0.9 parts of nylon acid diisobutyl ester, 1.0 parts of cross-linked silicone anti-sticking agent, 0.6 parts of aliphatic isocyanate cross-linking agent, stir completely evenly, add 6.0 parts of toluene, control the surface coating viscosity to 7500cps, filter the material to obtain anti-stick surface coating glue.

[0097] This embodiment provides a nylon fabric processing method based on the above-mentioned glue:

[0098] (1) Waterproof finishing: Use waterproof agent to pad the 620D high-strength nylon filament Oxford cloth, double dip and double padding, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4;

[0099] (2) The waterproof fabric is calendered twice with a calender at a pressure of 9 MPa, a temperature of 160°C, and a speed of 28 m / min;

[0100] (3) First coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (2) above using a floating knife coating machine, dry at 130-140°C for 1.0 minute, and dry weight gain of 55 g / m 2 ;

[0101] (4) Second coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (3) above using a floating knife coating machine, dry at 130-140°C for 1.1 minutes, and dry weight gain of 35 g / m 2 ;

[0102] (5) Anti-adhesive coating: The anti-adhesive coating in the treated glue solution is applied to the fabric treated in step (4) above by a floating knife coating machine, and then dried at 150-165°C for 1.2 minutes to obtain a dry weight gain of 8 g / m 2 .

[0103] Example 3

[0104] The present embodiment provides a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, including: a flame-retardant base coating adhesive and an anti-stick surface coating adhesive.

[0105] (1) Preparation of ultrafine flame retardant powder

[0106] Raw materials by weight

[0107] 80 parts of decabromodiphenylethane, 20 parts of antimony trioxide, 8 parts of zinc borate, and 27 parts of melamine cyanurate (MCA) were put into a planetary ball mill and ground for 13 hours. The particle size was D 50 0.5μm, ultra-fine flame retardant powder.

[0108] (2) Preparation of flame retardant primer

[0109] Raw materials by weight

[0110] Take 25 parts of toluene, add 1.0 parts of dispersant into toluene, stir to fully dissolve, then add 50 parts of ultrafine flame retardant powder obtained in the above step (1), disperse until completely uniform; then add 40 parts of two-component polyether polyurethane coating primer, stir evenly, then add 4.0 parts of nylon acid diisobutyl ester, 2.8 parts of tear inhibitor, 3.2 parts of butylated melamine resin, 1.6 parts of p-toluenesulfonic acid catalyst, 0.65 parts of aliphatic isocyanate crosslinking agent, stir completely evenly, add 0 parts of toluene, control the viscosity of the primer to 9700cps, filter the material, and obtain a flame retardant primer.

[0111] (3) Preparation of anti-stick surface coating

[0112] Raw materials by weight

[0113] Take 35 parts of toluene, add 0.25 parts of dispersant to toluene, stir to fully dissolve, then add 3.0 parts of high molecular weight spherical polyethylene powder, disperse until completely uniform; then add 3.0 parts of spherical silica, continue to disperse until completely uniform; then add 100 parts of one-component polyether polyurethane coating surface glue, stir evenly, then add 0.8 parts of nylon acid diisobutyl ester, 2.0 parts of cross-linked silicone anti-sticking agent, 0.7 parts of aliphatic isocyanate cross-linking agent, stir completely evenly, add 2.5 parts of toluene, control the surface coating viscosity to 7000cps, filter the material to obtain anti-stick surface coating glue.

[0114] This embodiment provides a nylon fabric processing method based on the above-mentioned glue:

[0115] (1) Waterproof finishing: Use waterproof agent to pad the 650D high-strength nylon filament Oxford cloth, double dip and double padding, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4;

[0116] (2) The waterproof fabric is calendered twice with a calender at a pressure of 11 MPa, a temperature of 160°C, and a speed of 25 m / min;

[0117] (3) First coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (2) above using a floating knife coating machine, dry at 130-140°C for 1.1 minutes, and dry weight gain of 55 g / m 2 ;

[0118] (4) Second coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (3) above using a floating knife coating machine, dry at 130-140°C for 0.9 minutes, and dry weight gain of 30 g / m 2 ;

[0119] (5) Anti-adhesive coating: The anti-adhesive coating in the treated glue solution is applied to the fabric treated in step (4) above by a floating knife coating machine, and then dried at 150-165°C for 1.2 minutes to obtain a dry weight gain of 10 g / m 2 .

[0120] Example 4

[0121] The present embodiment provides a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, including: a flame-retardant base coating adhesive and an anti-stick surface coating adhesive.

[0122] (1) Preparation of ultrafine flame retardant powder

[0123] Raw materials by weight

[0124] 85 parts of decabromodiphenylethane, 23 parts of antimony trioxide, 7 parts of zinc borate, and 28 parts of melamine cyanurate (MCA) were put into a planetary ball mill and ground for 15 hours. The particle size was D 50 0.3μm, ultra-fine flame retardant powder.

[0125] (2) Preparation of flame retardant primer

[0126] Raw materials by weight

[0127] Take 30 parts of toluene, add 0.8 parts of dispersant into toluene, stir to fully dissolve, then add 45 parts of ultrafine flame retardant powder obtained in the above step (1), disperse until completely uniform; then add 45 parts of two-component polyether polyurethane coating primer, stir evenly, then add 4.0 parts of nylon acid diisobutyl ester, 3.0 parts of tear inhibitor, 3.8 parts of butylated melamine resin, 1.9 parts of p-toluenesulfonic acid catalyst, 0.8 parts of aliphatic isocyanate crosslinking agent, stir completely evenly, add 1.0 parts of toluene, control the viscosity of the primer to 9800cps, filter the material, and obtain a flame retardant primer.

[0128] (3) Preparation of anti-stick surface coating

[0129] Raw materials by weight

[0130] Take 40 parts of toluene, add 0.2 parts of dispersant into toluene, stir to fully dissolve, then add 2.0 parts of high molecular weight spherical polyethylene powder, disperse until completely uniform; then add 3.5 parts of spherical silica, continue to disperse until completely uniform; then add 100 parts of one-component polyether polyurethane coating surface glue, stir evenly, then add 0.5 parts of nylon acid diisobutyl ester, 1.5 parts of cross-linked silicone anti-sticking agent, 0.8 parts of aliphatic isocyanate cross-linking agent, stir completely evenly, add 0 parts of toluene, control the surface coating viscosity to 7800cps, filter the material to obtain anti-stick surface coating glue.

[0131] This embodiment provides a nylon fabric processing method based on the above-mentioned glue:

[0132] (1) Waterproof finishing: Use waterproof agent to pad the 650D high-strength nylon filament Oxford cloth, double dip and double padding, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4;

[0133] (2) The waterproof fabric is calendered twice with a calender at a pressure of 10 MPa, a temperature of 170°C, and a speed of 25 m / min;

[0134] (3) First coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (2) using a floating knife coating machine, dry at 130-140°C for 0.9 minutes, and dry weight gain of 50 g / m 2;

[0135] (4) Second coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (3) above using a floating knife coating machine, dry at 130-140°C for 1.2 minutes, and dry weight gain of 40 g / m 2 ;

[0136] (5) Anti-adhesive coating: The anti-adhesive coating in the treated glue solution is applied to the fabric treated in step (4) above by a floating knife coating machine, and then dried at 150-165°C for 1.2 minutes to obtain a dry weight gain of 8 g / m 2 .

[0137] Example 5

[0138] The present embodiment provides a high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, including: a flame-retardant base coating adhesive and an anti-stick surface coating adhesive.

[0139] (1) Preparation of ultrafine flame retardant powder

[0140] Raw materials by weight

[0141] 90 parts of decabromodiphenylethane, 30 parts of antimony trioxide, and 30 parts of melamine cyanurate (MCA) were put into a planetary ball mill and ground for 15 hours. The particle size was D 50 0.2μm, ultra-fine flame retardant powder.

[0142] (2) Preparation of flame retardant primer

[0143] Raw materials by weight

[0144] Take 28 parts of toluene, add 0.7 parts of dispersant into toluene, stir to fully dissolve, then add 50 parts of ultrafine flame retardant powder obtained in the above step (1), disperse until completely uniform; then add 50 parts of two-component polyether polyurethane coating primer, stir evenly, then add 3.5 parts of nylon acid diisobutyl ester, 2.5 parts of tear inhibitor, 4.0 parts of butylated melamine resin, 2.0 parts of p-toluenesulfonic acid catalyst, 0.7 parts of aliphatic isocyanate crosslinking agent, stir completely evenly, add 5.0 parts of toluene, control the viscosity of the primer to 9400cps, filter the material, and obtain a flame retardant primer.

[0145] (3) Preparation of anti-stick surface coating

[0146] Raw materials by weight

[0147] Take 36 parts of toluene, add 0.45 parts of dispersant to toluene, stir to fully dissolve, then add 2.5 parts of high molecular weight spherical polyethylene powder, disperse until completely uniform; then add 4.5 parts of spherical silica, continue to disperse until completely uniform; then add 100 parts of one-liquid polyether polyurethane coating surface glue, stir evenly, then add 1.0 parts of nylon acid diisobutyl ester, 1.8 parts of cross-linked silicone anti-sticking agent, 1.0 parts of aliphatic isocyanate cross-linking agent, stir completely evenly, add 4.0 parts of toluene, control the surface coating viscosity to 7700cps, filter the material to obtain anti-stick surface coating glue.

[0148] This embodiment provides a nylon fabric processing method based on the above-mentioned glue:

[0149] (1) Waterproof finishing: Use waterproof agent to pad the 650D high-strength nylon filament Oxford cloth, double dip and double padding, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4;

[0150] (2) The waterproof fabric is calendered twice with a calender at a pressure of 11 MPa, a temperature of 150°C, and a speed of 20 m / min;

[0151] (3) First coat of flame retardant primer: Apply the flame retardant primer in the treated glue solution to the fabric treated in step (2) above using a floating knife coating machine, dry at 130-140°C for 1.2 minutes, and dry weight gain of 60 g / m 2 ;

[0152] (4) Second coat of flame retardant primer: Apply the primer in the treated glue solution to the fabric treated in step (3) above using a floating knife coating machine, dry at 130-140°C for 0.8 minutes, and dry weight gain of 25 g / m 2 ;

[0153] (5) Anti-adhesive coating: The anti-adhesive coating in the treated glue solution is applied to the fabric treated in step (4) above by a floating knife coating machine, and then dried at 150-165°C for 1.1 minutes to obtain a dry weight gain of 10 g / m 2 .

[0154] Comparative Example 1

[0155] This comparative example provides an existing polyester fabric product and a processing method thereof:

[0156] 1000D high-strength polyester filament Oxford cloth, the surface of which is subjected to water-repellent finishing → two-time calendering → two-time flame-retardant primer coating → one-time top coating to obtain high-strength flame-retardant coated fabric.

[0157] Comparative Example 2

[0158] This comparative example provides an existing nylon fabric product and a processing method thereof:

[0159] The surface of 500D high-strength nylon filament Oxford cloth is processed through water-repellent finishing → two-time calendering → two-time flame-retardant primer coating → one-time top coating to obtain high-strength flame-retardant coated fabric.

[0160] Comparative Example 3

[0161] This comparative example provides an existing nylon fabric product and a processing method thereof:

[0162] 650D high-strength nylon filament Oxford cloth, the surface of which is water-repellent finishing → two-time calendering → two-time flame-retardant primer coating → one-time surface coating to obtain high-strength flame-retardant coated fabric. This high-strength flame-retardant coated fabric is the coated fabric of Chongqing 3533 Printing and Dyeing Garment General Factory Co., Ltd.

[0163] The test results are shown in Table 1 below.

[0164] Table 1

[0165]

[0166]

[0167] Dry weight gain and gram weight test: according to GB / T4669-2008 Textile woven fabric mass per unit length and mass per unit area;

[0168] Vertical flame retardant performance test: According to GB / T5455-2014 textile combustion performance vertical direction damage length, smoldering and after-flaming time determination;

[0169] Breaking strength test: according to GB / T 3923.1-2013 Tensile properties of fabrics Part 1: Determination of breaking strength and elongation at break (strip method);

[0170] Tear strength test: according to GB / T3917.3-2009 Tear properties of fabrics Part 3: Determination of tear strength of trapezoidal specimens;

[0171] Hydrostatic pressure test: Determination of water resistance of coated fabrics according to FZ / T01004-2008;

[0172] Low temperature resistance test: according to FZ / T01007-2008, determination of low temperature resistance of coated fabrics;

[0173] Washing fastness test: according to GB / T8629-20014A Textile Testing Home Washing and Drying Procedure;

[0174] Anti-adhesion test: according to FZ / T01063-2008 Determination of anti-adhesion of coated fabrics;

[0175] Abrasion resistance test: according to ASTM D3884-2009 test method for abrasion resistance of fabrics (rotating platform, double-head method);

[0176] Water stain test: Water stain test according to GB / T4745-2012 Textile fabric surface moisture resistance determination.

[0177] It can be seen from the comparison in the above table that the fabric obtained by the present invention has a low gram weight, which is less than 330g / m 2 , which is significantly lower than other fabrics in weight; at low weight, it maintains excellent flame retardant properties, the afterflaming time is less than 1 second, the smoldering time is 0 second, and the damaged length is kept within 80mm; the breaking strength is high, both in the warp direction are above 3100N, and both in the weft direction are above 3000N; the tearing strength is high, both in the warp direction are above 420N, and both in the weft direction are above 320N; the hydrostatic pressure is high, the initial water pressure is above 70Kpa, and after 5 washings, it is still maintained above 30Kpa; the low temperature resistance is good, there is no crack at -40℃; the anti-adhesion property is good, there is no adhesion; the wear resistance is excellent, all are wear-resistant for more than 10,000 times; the water-wetting property reaches level 4. The fabric obtained by the present invention not only maintains a relatively low gram weight, but is also significantly superior to comparative products in terms of flame retardancy, tear strength, hydrostatic pressure, low temperature resistance, and wear resistance, achieving the combination of relatively low gram weight, cold resistance, water pressure resistance, flame retardancy, high strength, washability, wear resistance, and anti-adhesion.

[0178] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive, characterized in that: Including flame retardant base coating and anti-stick surface coating; The raw materials of the flame retardant primer include, by weight: 25-40 parts of toluene, 0.5-1.0 parts of dispersant, 40-50 parts of ultrafine flame retardant powder, 40-50 parts of two-component polyether polyurethane coating primer, 2.0-4.0 parts of diisobutyl nylonate, 2.0-3.0 parts of tearing agent, 3.2-4.0 parts of butylated melamine resin, 1.6-2.0 parts of p-toluenesulfonic acid catalyst, and 0.6-0.8 parts of aliphatic isocyanate crosslinking agent; The raw materials of the anti-stick surface coating glue include, by weight: 30-50 parts of toluene, 0.2-0.5 parts of dispersant, 2.0-3.0 parts of high molecular weight spherical polyethylene powder, 3.0-5.0 parts of spherical silica, 100 parts of one-component polyether polyurethane coating surface glue, 0.5-1.0 parts of nylon acid diisobutyl ester, 1.0-2.0 parts of cross-linked silicone anti-stick agent, and 0.5-1.0 parts of aliphatic isocyanate cross-linking agent.

2. The high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment glue according to claim 1, characterized in that: The ultrafine flame retardant powder is made of 60-90 parts of decabromodiphenylethane, 20-30 parts of antimony trioxide and 20-30 parts of melamine cyanurate, and is ground into a particle size D by a ball mill. 50 ≤1μm, and the ultrafine flame retardant powder is obtained.

3. The high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment glue according to claim 2, characterized in that: Replace 5-15 parts of antimony trioxide with an equal amount of zinc borate.

4. The high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive according to claim 1, characterized in that: The dispersant is a long-chain fatty amide solution; The solid content of the one-component polyether polyurethane coating surface adhesive is (30±2)%; The solid content of the two-component polyether polyurethane coating primer is (60±5)%; The anti-tear agent is KSL-100; The solid content of the butylated melamine resin is (54-60) %; The solid content of the p-toluenesulfonic acid catalyst is (20±0.5)%; The solid content of the aliphatic isocyanate crosslinking agent is (75±2)%; The high molecular weight spherical polyethylene powder has a particle size D 50 ≤30μm; The spherical silicon dioxide powder has a particle size D 50 ≤10μm; The cross-linked organic silicon anti-adhesive agent is a cross-linked organic silicon resin with a molecular weight of 1500-2500.

5. The high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive according to any one of claims 1 to 4, characterized in that: The preparation method of the flame retardant primer comprises: adding 0.5-1.0 parts of a dispersant to 25-30 parts of toluene, stirring to fully dissolve, then adding 40-50 parts of ultrafine flame retardant powder, dispersing until completely uniform; then adding 40-50 parts of a two-component polyether polyurethane coating primer, stirring evenly, then adding 2.0-4.0 parts of diisobutyl nylon acid, 2.0-3.0 parts of a tearing agent, 3.2-4.0 parts of butylated melamine resin, 1.6-2.0 parts of a p-toluenesulfonic acid catalyst and 0.6-0.8 parts of an aliphatic isocyanate crosslinking agent, stirring evenly, adding 0-10 parts of toluene, controlling the viscosity to 9000-10000 cps, filtering the material, and obtaining the flame retardant primer; The preparation method of the anti-stick surface coating comprises: adding 0.2-0.5 parts of a dispersant into 30-40 parts of toluene, stirring to fully dissolve, then adding 2.0-3.0 parts of a high molecular weight spherical polyethylene powder, dispersing until completely uniform; then adding 3.0-5.0 parts of spherical silicon dioxide, continuing to disperse until completely uniform; then adding 100 parts of a one-component polyether polyurethane coating surface adhesive, stirring evenly, then adding 0.5-1.0 parts of nylon acid diisobutyl ester, 1.0-2.0 parts of a cross-linked organic silicon anti-sticking agent and 0.5-1.0 parts of an aliphatic isocyanate cross-linking agent, stirring evenly, adding 0-10 parts of toluene, controlling the viscosity to 7000-8000cps, filtering the material, and obtaining the anti-stick surface coating.

6. Use of the high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric treatment adhesive according to any one of claims 1 to 5 in the production of equipment and backpacks.

7. The use according to claim 6, characterized in that: The nylon fabric is 620D-650D high-strength nylon filament Oxford cloth.

8. A method for processing high-strength, cold-resistant, water-pressure-resistant, flame-retardant, low-weight nylon fabric, characterized in that: The method comprises: After the nylon fabric is subjected to waterproof finishing and calendering treatment, the flame retardant base coating glue and the anti-sticking surface coating glue as claimed in any one of claims 1 to 5 are sequentially coated.

9. The method for processing high-strength, cold-resistant, water-pressure-resistant, flame-retardant, and low-weight nylon fabric according to claim 8, characterized in that: The method comprises the following steps: (1) Waterproof finishing: Use waterproof agent to pad the nylon fabric, double dip and double pad, padding rate 40-50%, 120-150-170-170℃ drying for 1.0 minute, water level ≥ 4; (2) The waterproof fabric is calendered twice with a calender at a pressure of 9-11 MPa, a temperature of 150-170°C, and a speed of 20-30 m / min; (3) First coat of flame retardant primer: The flame retardant primer is coated on the fabric treated in step (2) using a floating knife coating machine, and then dried at 130-140°C for 0.8-1.2 minutes to obtain a dry weight gain of 50-60 g / m 2 ; (4) Second coat of flame retardant primer: The flame retardant primer is coated on the fabric treated in step (3) using a floating knife coating machine, and dried at 130-140°C for 0.8-1.2 minutes to a dry weight gain of 20-40 g / m 2 ; (5) Anti-adhesive coating: The anti-adhesive coating is applied to the fabric treated in step (4) by a floating knife coating machine, and dried at 150-165° C. for 1.0-1.2 minutes to obtain a dry weight gain of 8-10 g / m 2 .

10. The method for processing high-strength, cold-resistant, water-pressure-resistant, flame-retardant, and low-weight nylon fabric according to claim 9, characterized in that: The waterproofing agent is an organic fluorine waterproofing agent.